“Estrategias didácticas para la estimulación del lenguaje verbal de los niños de 3 a 4 años de inicial” - Evelyn Estefania, Guanoluisa Llamuca (2022)
The stimulation of verbal language in children refers to the development of skills and abilities developed through didactic strategies awakening sensory, motor, cognitive, and language stimuli in the child. The present investigation is carried out in the Educational Unit "Pujilí" belonging to Cotopaxi Province, Pujilí Canton; its problem lies in the children of initial education from 3 to 4 years, since they present difficulties in the language, it was observed that the teacher does not frequently apply exercises or activities that help students work on the area of language since they work in a general way without realizing the student's need. The general objective of this research was to identify the didactic strategies currently applied by teachers for the development of verbal language in children of Initial Education, using qualitative research as an approach, which allowed a deep analysis of the strategies used, the bibliographic-documentary design, and the field design where it is based on the systematic, rigorous and in-depth review of the subject, the type of research was exploratory, it allows knowing what activities they use with children such as oral phonatory exercises, soft palate, lipsticks, breathing and blowing, reading stories, reciting poems, description of pictograms or theater and plastic arts; descriptive work was done with the 25 students 10 girls and 15 boys, and 1 teacher, concluding on the didactic strategies, how they should be applied with greater emphasis according to the student's need; in this case, activities should be determined to the development of communication and social relationships, allowing the child to express their emotions and ideas towards others.